1999
DOI: 10.1115/1.1303707
|View full text |Cite
|
Sign up to set email alerts
|

A Correlation for Tip Leakage Blockage in Compressor Blade Passages

Abstract: Three-dimensional multistage Navier–Stokes simulations for compressor components, rigs, and cascades have been analyzed to gain insight into the tip leakage blockage evolution. From pitch-averaged flow quantities the local displacement caused by tip leakage is determined by means of a novel technique. Close to the throat an additional displacement of about 1–4 percent axial chord is observed for unchoked flow conditions. With tip gap height, stagger, and inlet Mach number as governing variables, a correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It is of course to keep in mind that stall onset in transonic compressors is in many cases due to flow features linked to the clearance vortex at the blade tip (Vo [7]). In subsonic compressors the tip clearance vortex generates a region of very low axial velocity, also known as blockage (Storer [8,9], Hoeger [10,11], Khalid [12]). However, compared to subsonic cases there is a significant stronger vortex in supersonic ones.…”
Section: Nomenclature Mmentioning
confidence: 99%
“…It is of course to keep in mind that stall onset in transonic compressors is in many cases due to flow features linked to the clearance vortex at the blade tip (Vo [7]). In subsonic compressors the tip clearance vortex generates a region of very low axial velocity, also known as blockage (Storer [8,9], Hoeger [10,11], Khalid [12]). However, compared to subsonic cases there is a significant stronger vortex in supersonic ones.…”
Section: Nomenclature Mmentioning
confidence: 99%
“…Techniques such as blade tip reshaping, magazine treatment, suction, blowing treatment, plasma discharge, and blade tip winglet technology are prevalently implemented as active and passive measures for controlling blade tip leakage flow.Numerous studies have been carried out by many scholars for the blade tip leakage flow control methods and aerodynamic noise reduction.A.For instance, Maaloum et al [ 1 ] found the important noise sources corresponding to the high pressure fluctuation region located at the blade tip using potential flow methods; Jung,J.H [ 2 ] analyzed the flow structure at the blade tip due to the position of the winglets and confirmed the existence of an optimal blade tip clearance. Hoeger [ 3 ] pointed out the existence of peak blockages in the channel based on numerical simulation results of a large number of transonic compressor rotors and blade grilles,whose distribution characteristics were clearly influenced by the interaction of leakage vortices and excitation waves. Liu B [ 4 ] quantitatively analyzed the characteristics of the blockage distribution in the rotor channel under different measurement conditions, and the blade tip leakage blockage showed nonlinear and nonmonotonic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…46 Meanwhile, many empirical models have been proposed to estimate the tip blockage, loss production, or vortex trajectory caused by TLF in the tip region. 710 The influence of tip clearance size (TCS) on the flow structure of TLF is also a focus of many research efforts. It is found that the onset point of TLV is usually at the maximum loading of the blade and a higher TCS moves the position of the highest loading further downstream thus delaying the roll up of the TLV.…”
Section: Introductionmentioning
confidence: 99%